A Novel Scale for Assessment of Stroke Severity at Symptom Onset: Correlation With Neurological Deterioration and Outcome - Li, Qi; Deng, Lan; Huang, Cheng; Zhang, Wen-Yu; Zou, Ning; Cao, Du; Wei, Xiao; Qin, Xin-Yue (Frontiers in Neurology, 2021)
Objective: To propose a novel scale for assessment of stroke severity at symptom onset and to investigate whether it is associated with ultraearly neurological deterioration and function outcome. Methods: The Chongqing Stroke Scale (CQSS) was constructed based on key aspects of history, emphasizing language, motor function and level of consciousness to yield a total 0–11 scale. The diagnostic performance of the CQSS was assessed in 215 ischemic stroke patients between June 2017 and October 2017 in a tertiary hospital. Patients were included if they presented within 24 hours after onset of symptoms and they or their witness can recall the scenario at symptom onset. Ultraearly neurological deterioration (UND) was defined as increase≥2 points on CQSS between symptom onset and admission. Function outcomes were assessed using 3-month modified Rankin scale (mRS). The correlation between CQSS score and baseline NIHSS score was assessed. The sensitivity, specificity, positive and negative predictive values of CQSS for the outcomes were calculated. Logistic regression was used to test the association between the score on CQSS and the outcomes. and functional outcome. Results: A total of 215 patients with available CQSS scores were included. Baseline CQSS scores at symptom onset were correlated with the admission NIHSS score (r=0.56, p<0.001) and functional outcome at 3 months (r=0.47, p<0.001). Baseline CQSS≥6 was an independent predictor of functional outcome at 3 months(odds ratio, 12.61; 95% confidence interval 5.68-27.97, P＜0.001). UND was observed in 20 (9.30%) patients. The 90-day mortality was significantly higher in patients with UND than those without (25.0% vs 8.2%, P<0.001). After adjusting for age, admission systolic blood pressure, hypertension and diabetes, UND independently predicts poor functional outcome in multivariate logistic regression model (odds ratio, 9.69; 95% confidence interval 3.19-29.45, p<0.001). Conclusions: The newly developed CQSS was a simple and easy-to-perform scale that allows quantitative evaluation of the stroke severity at symptom onset as well as assessment of ultraearly neurological deterioration before hospital admission. It is associated with NIHSS and predicts functional outcome in patients with acute ischemic stroke.